The Economics of Money, Banking, and Financial Markets - Mishkin (Addison Wesley, 2012)
The Sixth Edition of The Economics of Money, Banking, and Financial Markets represents the most extensive revision to date of this market-leading textbook. Drawing from his service as Executive Vice President and Director of Research at the Federal Reserve Bank of New York, Mishkin provides fresh, thoroughly updated coverage of and many new insights into the monetary policy process, the operation of the Federal Reserve, the regulation and supervision of the financial system, and the internationalization of financial markets. He provides an applications-oriented perspective with numerous applications and special topic boxes that increase students' interest by showing them how to apply theory to the real world. In addition, Mishkin provides a careful, step-by-step development of models, an approach found in the best principles of economic textbooks, that makes it easier for students to learn. Over 400 end-of-chapter problems aid in reinforcing the essential chapter content